Consumers' perception on Islamic home financing: empirical evidences on Bai Bithaman Ajil(BBA) and diminishing partnership (DP) modes of financing in Malaysia - Abdul Razak, Dzuljastri; Md Taib, Fauziah (Emerald Group Publishing Limited, 2011)
The purpose of this paper is to examine customers’ perception on two modes of home financing namely Bai Bithaman Ajil (BBA), debt-based financing, and diminishing partnership (DP), an equity-based financing, focusing on the concepts used, methods of computation and pricing, Shariah compliant, justice and equality, societal well being and equitable distribution of wealth and income and preference for the products.